Biomarkers to predict the outcomes of surgical intervention for aortic dissection - Abanob G. Hanna; Fabian Jimenez Contreras; Omar M. Sharaf; Griffin P. Stinson; Philip J. Hess (Journal of Cardiothoracic Surgery)
Abstract Purpose Aortic dissections and repairs are associated with high rates of mortality. The aim of this review is to summarize the literature concerning the prognostic ability of various preoperative biomarkers for patients undergoing surgical repair of the thoracic and abdominal aorta to elucidate whether these biomarkers could improve the selection of surgical candidates. Methods Relevant biomarkers were selected if they had predictive value in inflammatory disease processes and/or cardiovascular disease. Full-text articles available in English on PubMed that related these biomarkers to the prognosis of aortic repair following aortic dissection were examined. Results For patients who underwent repair for type A dissection, a preoperative elevated SII was associated with inferior 30-day survival (hazard ratio: 3.532, 95% confidence interval: 1.719–7.255, p = 0.001) and increased rates of adverse cardiovascular events. Elevated preoperative IL-6 and D-dimer levels were independently associated with single-organ dysfunction, multiorgan dysfunction, and death. The use of a combination of markers was a stronger predictor. The areas under the curve (AUCs) for the specified IL-6 and D-dimer cutoff values were 0.901 and 0.817, respectively, whereas the AUC reached 0.936 when IL-6 was combined with D-dimer. For patients who underwent thoracic endovascular aortic repair (TEVAR) for type B dissection, an elevated postoperative systemic immune-inflammation index (SII) was an independent risk factor for aorta-related complications, graft failure, and significantly inferior freedom from aortic-related mortality. A combination of elevated preoperative and postoperative SII values was again predictive of in-hospital adverse outcomes and follow-up complications, including endoleaks, branch artery stenosis, distal aortic expansion, aortic rupture, and death (p = 0.0016). An elevated preoperative neutrophil‒leukocyte ratio (NLR) is associated with an increased incidence of early postoperative adverse events and poor survival. Conclusions Inflammatory markers seem to have predictive ability for postoperative outcomes after aortic repair in type A dissections. Further studies should compare these biomarkers to determine the best predictive marker for individual disease states and surgeries.